Blinded Evaluation of Endoscopic Skill and Instructability After Implementation of an Endoscopic Simulation Experience. Issue 6 (November 2019) - Stephenson, Elizabeth D.; Farquhar, Douglas R.; Masood, Maheer M.; Capra, Gregory; Kimple, Adam; Ebert, Charles S.; Thorp, Brian D.; Zanation, Adam M.
Background: Interest in endoscopic simulation is increasing. Past studies have used virtual reality or nonhuman models or residents with varying experience. Our aim was to evaluate the effect of simulation on procedural and psychomotor competence of medical students—surgical novices—performing endoscopic tasks on human cadavers and assess student perceptions. Methods: Students (n = 22) completed a baseline sinus model skill evaluation graded by 2 blinded Rhinology fellows. Intervention and control groups with equal baselines were assigned. Intervention students practiced endoscopic tasks on the model for 45 minutes minimum over 2 weeks. All students reviewed sinus anatomy/disease and sinus surgery materials. The final cadaver evaluation was similar to the baseline. Fellows graded students on anatomy identification (sinuses, turbinates), psychomotor (navigation, camera alignment, instrument handling), and timed procedural (sinus object retrieval) skills, confidence, and instructability via fellow-guided frontal balloon placement. Results: Participants included 16 males (72.7%) and 6 females (27.3%). Intervention and control groups contained 10 (45.4%) and 12 (54.6%) students, respectively. Intervention group final "Total Psychomotor" scores were higher (10.1/15 vs 7.8/15, P = .0231). "Surgical confidence" was 3.3/5 versus 2.5/5, and "Instructability" was 3.9/5 versus 3.4/5 in intervention versus control groups, respectively ( P < .050). Multivariate regression analysis demonstrated superior psychomotor skills, navigation, and confidence in the intervention group ( P < .036). Activity perception scores were higher in intervention students versus controls, 26.13 versus 18.36/40 ( P = .022). Conclusion: In surgical novices, endoscopic simulation leads to superior endoscopic navigation and task performance in cadavers. This simulation presents a novel method for incorporating Otolaryngology simulation in medical student education.